2014
DOI: 10.1155/2014/321209
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte-Secreted Matricellular Proteins in CNS Remodelling during Development and Disease

Abstract: Matricellular proteins are secreted, nonstructural proteins that regulate the extracellular matrix (ECM) and interactions between cells through modulation of growth factor signaling, cell adhesion, migration, and proliferation. Despite being well described in the context of nonneuronal tissues, recent studies have revealed that these molecules may also play instrumental roles in central nervous system (CNS) development and diseases. In this minireview, we discuss the matricellular protein families SPARC (secre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
125
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(125 citation statements)
references
References 168 publications
(217 reference statements)
0
125
0
Order By: Relevance
“…Connective tissue growth factor (CTGF) and RhoA are putative targets of miR-133b and are known to suppress neurite growth (118). In vitro, incubation of cortical neurons with miR-133b-elevated exosomes downregulated RhoA and enhanced neurite outgrowth, whereas treatment of astrocytes with miR-133b-elevated exosomes suppressed CTGF, which is mainly expressed by astrocytes (119,124). Collectively, these data indicate that MSCderived exosomes may be used as vehicles to transport miRNAs that modulate genes in the recipient neurons and astrocytes.…”
Section: Hsc-exosomes and Therapiesmentioning
confidence: 99%
“…Connective tissue growth factor (CTGF) and RhoA are putative targets of miR-133b and are known to suppress neurite growth (118). In vitro, incubation of cortical neurons with miR-133b-elevated exosomes downregulated RhoA and enhanced neurite outgrowth, whereas treatment of astrocytes with miR-133b-elevated exosomes suppressed CTGF, which is mainly expressed by astrocytes (119,124). Collectively, these data indicate that MSCderived exosomes may be used as vehicles to transport miRNAs that modulate genes in the recipient neurons and astrocytes.…”
Section: Hsc-exosomes and Therapiesmentioning
confidence: 99%
“…In vitro studies showed that ischemic brain tissue elevated miR-133b levels in MSC-released exosomes. In the brain, CTGF is mainly expressed by astrocytes [71]. The treatment of astrocytes with the exosomes containing high levels of miR-133b downregulated CTGF expression, while incubation of neurons with the exosomes reduced RhoA expression and promoted neurite outgrowth [72].…”
Section: Exosomes and Brain Remodelingmentioning
confidence: 99%
“…The distribution and composition of these ECM components in the developing rodent brain is changing during embryonal and postnatal phases and reaches a mature stage at postnatal day 20. [25] However, disease-associated remodeling of the CNS ECM has been observed after injury, [25][26][27][28] suggesting that growing primary neoplasms in the brain may also alter the surrounding ECM. Relatively little change in the expression levels of a small set of proteins in normal brain tissue and in brain tissue surrounding invasive glioblastoma was observed in a recent study, [29] except for Tenascin-R and CD168, which were both up-regulated.…”
Section: Biophysical Properties Of the Brain Microenvironmentmentioning
confidence: 99%
“…[43] Another decisive input could stem from astrocytes activated by the neoplastic lesion and the consequent up-regulation of matricellular proteins such as secreted protein acidic and rich in cys-teins (SPARC) in astrocytoma [44] and medulloblastoma [45] or connective tissue growth factor in glioma, [46] which jointly with additional matricellular proteins remodel neuronal tissue during development or after brain injury. [28] Significantly, the concept of reciprocal stimulation of tumor cells and astrocytes was recently also identified in metastatic melanoma, which elicits an inflammatory cytokine response in astrocytes that facilitates brain metastasis. [47] Combined, these studies emphasize the importance of incorporating environmental parameters into experimental protocols to explore their contribution to the proteomic landscape and the functional outcomes of primary brain tumors.…”
Section: Biophysical Properties Of the Brain Microenvironmentmentioning
confidence: 99%